2019
DOI: 10.1371/journal.pone.0221161
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of postnatal care utilization in Tigray, Northern Ethiopia: A community based cross-sectional study

Abstract: Introduction Globally, 289,000 women die from complications related to pregnancy, childbirth, or the postnatal period every year. Two-thirds of all maternal deaths occur during the first six weeks following birth and more than two thirds of newborn deaths occur during the first week of life, These statistics underscore the importance of postnatal care, an often neglected service according to the World Health Organization (WHO). The purpose of this study was to assess the factors associated with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
43
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 14 publications
(21 reference statements)
14
43
8
2
Order By: Relevance
“…The current analysis shows that mothers from rural areas are less likely to receive FPNC compared to mothers in urban areas. This is similar to what was reported in other studies in Ethiopia 32,36 The other factor which detected strong positive association in several studies around the globe was the institutional delivery 6,25,31,44 . We could not demonstrate that association due to the fact that more than 99% deliveries occurred in institutions.…”
Section: Background Characteristicssupporting
confidence: 91%
“…The current analysis shows that mothers from rural areas are less likely to receive FPNC compared to mothers in urban areas. This is similar to what was reported in other studies in Ethiopia 32,36 The other factor which detected strong positive association in several studies around the globe was the institutional delivery 6,25,31,44 . We could not demonstrate that association due to the fact that more than 99% deliveries occurred in institutions.…”
Section: Background Characteristicssupporting
confidence: 91%
“…Mothers likely received PNC before discharge, would be delivered by cesarean section. Previous studies in rural Ethiopia [12][13][14] also showed women who had cesarean births used more postpartum care than those who had vaginal births. The result of this study revealed that the use of PNC services has been significantly influenced by knowledge of antepartum, intrapartum, or postpartum danger signs This is in line with the studies carried out in Ethiopia [13,14].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in rural Ethiopia [12][13][14] also showed women who had cesarean births used more postpartum care than those who had vaginal births. The result of this study revealed that the use of PNC services has been significantly influenced by knowledge of antepartum, intrapartum, or postpartum danger signs This is in line with the studies carried out in Ethiopia [13,14]. An integrative review by Adams and Smith suggested that awareness about pregnancy, childbirth, and/or postpartum complications is one of the common determinants of postpartum care use in developing countries [27].…”
Section: Discussionmentioning
confidence: 95%
“…There have been some studies that examined why PNC service utilisation remains low in Ethiopia. Some of these studies had a small sample size [ 15 , 16 ] and others covered a very small geographical area [ 17 , 18 ] that may put the representativeness of the studies and generalisability of the findings into question. Although there have been four rounds of the EDHS, studies that used these data have concentrated on the 2016 survey [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%